Tris(o-chlorobenzyl)[3-(4-methoxybenzoyl)propionato-kappa O]tin(IV) - Keng, T.C.; Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2010)
The tin atom in the title compound, [Sn(C7H6Cl)(3)(C11H11O4)], exists in a distorted tetrahedral coordination environment. The carboxylate anion is equally disordered over two positions.